Adsorbed Conformations of PCE Superplasticizers in Cement Pore Solution Unraveled by Molecular Dynamics Simulations. Issue 1 (December 2017) - Hirata, Tsuyoshi; Ye, Jun; Branicio, Paulo; Zheng, Jianwei; Lange, Alex; Plank, Johann; Sullivan, Michael
Abstract The conformations of polycarboxylate ether (PCE) type superplasticizer polymers adsorbed on the surface of MgO in cement pore solution are simulated by molecular dynamics (MD). Three types of PCEs commonly applied to concrete are simulated, namely a methacrylate type PCE (PCEM-P ), an allyl ether type PCE (PCEA-P ), and an isoprenyl ether type PCE (PCEI-P ) with ethylene oxide (EO) unit numbers (P ) of 25, 34 and 25, respectively. It is observed that the adsorbed layer thickness is inversely proportional to the experimentally measured adsorbed amount at the initial paste flow of 26 ± 0.5 cm. Simulation results indicate that the adsorbed layer thickness is sensitive to the initial polymer orientations against the model MgO surface. I.e., polymer molecules initially placed parallel/perpendicularly against the MgO surface gradually forms a train shaped or a loop and tail adsorption profile, respectively. As a result, the loop and tail shaped conformation gives a higher layer thickness.